2015
DOI: 10.1002/masy.201500058
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Control the Elution Behavior of PVA Cast Gels

Abstract: Summary: Poly(vinyl alcohol) (PVA) gels, prepared by a cast-drying method, show excellent swelling and mechanical properties. However, the elution of polymers from such gels is one of the major hindrances for practical applications. In this study, PVA cast gels were prepared from a PVA powder, with a high degree of polymerization and hydrolysis, under different temperatures and humidities. The swelling ratio, elution ratio, crystallinity, and microcrystallite size were evaluated, and these were compared with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Drying speed of sample D was lower than that of sample E because of higher relative humidity. It is indicated that low-speed drying leads to the growth of micro-crystalline structure and reinforcement of cross-linking in PVA-CD gel [20]. It is considered that extent of cross-linking in sample D is higher than that of sample E. If excess cross-linking is applied, protruding of PVA molecules was reduced and superficial hydration layer is not sufficiently formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drying speed of sample D was lower than that of sample E because of higher relative humidity. It is indicated that low-speed drying leads to the growth of micro-crystalline structure and reinforcement of cross-linking in PVA-CD gel [20]. It is considered that extent of cross-linking in sample D is higher than that of sample E. If excess cross-linking is applied, protruding of PVA molecules was reduced and superficial hydration layer is not sufficiently formed.…”
Section: Resultsmentioning
confidence: 99%
“…The drying conditions in the preparation of PVA-hybrid gels used in this study are listed in Table 1. It was reported that temperature and relative humidity during drying process are key factors for the formation of cross-linking and micro-crystalline structure of PVA-CD gel [19][20][21][22]. If we set the high temperature at the first step during drying process, the shape of PVA-CD and PVA-hybrid gels become undulated and we cannot use these specimens for friction test.…”
Section: Preparation Of Pva-hybrid Gelmentioning
confidence: 99%
“…83,84 The degree of crystallinity is defined as the ratio of the volume (or weight) of PVA microcrystallines to the total volume (or weight) of PVA, 28 which can be obtained using a range of different techniques. 85,86 In this article, the crystallinity was measured 87 using DSC (DSC8000; PerkinElmer) and a thermogravimetric analyzer (TGA; TGA4000; PerkinElmer). Two samples were cut from each dried sample.…”
Section: Experimental and Typical Properties Of Pva Gelsmentioning
confidence: 99%